In Vitro studies on antibacterial activity and phytochemical analysis of whole plant extracts of Stelleria media - Balendra Singh; Sharad Kumar Yadav (International Journal of Phytomedicine, 2010)
The whole plant extracts of Stelleria media were examined for the presence of alkaloids and phenolics with simultaneous study on the antimicrobial properties of these extracts. Investigation was carried out using four different concentration (62.5, 125, 250 and 500 mg/ml) of extract to determine the quantitative effectiveness. Preliminary evaluation of both the aqueous and the chloroform fractions showed a broad spectrum of activity ((p<0.05)) since the extracts inhibit the growth of both gram positive and gram negative bacterial isolates. Clinical isolates used in present investigation were E.coli, S.typhi, K. pneumonia, Staph. Aureus, Pseudomonas aeruginosa, Bacillus subtilis. The phytochemical analysis revealed the presence of alkaloids, saponins, tannins, flavonoids, cardiac glycosides, anthraquinones and cyanogenetic glycosides in varying concentration. Both the chloroform and aqueous extracts inhibited the growth of the test organisms with Salmonella typhi and E.coli showing the highest susceptibility but the pathogens were found to be less sensitive for chloroform extract in comparison to the aqueous extract which could be due to the domination of antimicrobial activity of water soluble polar compounds. This research supports the local use of the plant, Stelleria media for prophylactic and therapeutic purposes against bacterial infection.